Attribution of the impacts of the 2008 flooding in Cedar Rapids (Iowa) to anthropogenic forcing. (24th November 2020) - Villarini, Gabriele; Zhang, Wei; Quintero, Felipe; Krajewski, Witold F; Vecchi, Gabriel A
Abstract: The City of Cedar Rapids was significantly affected by the June 2008 flood. However, little is known about the role anthropogenic warming during this event, not only in terms of hydrologic response but also of impacts. Here we use a continuous distributed hydrologic model forced with precipitation with and without external forcing and show that the impacts of this flood were likely magnified because of increased anthropogenic warming; compared to the baseline scenario with the external forcing removed, this event was ∼1.28-fold larger in flood extent, an approximate 3.4-time larger in the number of affected buildings, and an estimated 5.8- and 7.1-time larger in structural and content damage, respectively. While much of the effort up to this point has focused on the attribution of the physical hazard, our results highlight the cascading increase of the contribution of the external forcing (mainly from anthropogenic forcing) moving from hazard to human impacts.